Untargeted liquid chromatography coupled with mass spectrometry reveals metabolic changes in nitrogen-deficient Isatis indigotica Fortune. (October 2019) - Cao, Yi-Wen; Qu, Ren-Jun; Miao, Yu-Jing; Tang, Xiao-Qing; Zhou, Ying; Wang, Lei; Geng, Li
Abstract: Isatis indigotica Fortune is a popular herb in traditional Chinese medicine, and various types of metabolites are the basis for its pharmacological efficacy. The biosynthesis and accumulation of these metabolites are closely linked to nitrogen availability; the benefits of low nitrogen application on the environment and herb quality are increasingly prominent. To analyze metabolic changes in the leaves and roots of I.indigotica in nitrogen deficiency conditions, and to identify the pathways and metabolites induced by low nitrogen availability, we used untargeted liquid chromatography coupled with mass spectrometry (UHPLC-TripleTOF) to obtain metabolomics profiling of I.indigotica under two N-deficiency treatments (0 kg/hm 2 ; 337.5 kg/hm 2 ) and normal nitrogen treatment (675 kg/hm 2 ). A total of 447 metabolites were annotated. Principal component analysis separated the three nitrogen treatments. A greater diversity of metabolites was observed in roots than in leaves under N-deficiency treatments, suggesting that roots have a more important function in low N tolerance. Differential metabolites were mainly enriched in purine metabolism, phenylpropanoid biosynthesis, the shikimate pathway, tryptophan metabolism, and flavonoid biosynthesis that notably induced only in leaves in low nitrogen stress. Moderate N-deficiency benefits carbohydrate accumulation, whereas accumulation of most amino acids decreases. Uniquely, L-tryptophan was maintained at a high concentration in N-deficiency conditions. Low nitrogen stress induced the accumulation of some specialized metabolites (matairesinol, dictamnine, 5-hydroxyindoleacetate (serotonin) in roots and vitexin, xanthohumol, sinapyl alcohol in leaves). N-deficiency also increased the accumulation of adenosine and quality indicators of I.indigotica (indirubin-indigo, epigoitrin and anthranilic acid) in a certain degree. Our findings showed that nitrogen deficiency modified roots and leaves conditions of I.indigotica, affecting both the primary and secondary metabolism. Moderate nitrogen reduction was beneficial to the accumulation of active ingredients. Our methods and analysis are expected to provide an insight regarding the diversity of metabolites and regulation of their synthesis in low nitrogen application, and better investigate the nitrogen deficiency effect on I.indigotica. Graphical abstract: Image 1049134 Highlights: A greater diversity of metabolites was observed in roots than in leaves under N-deficiency treatments. Differential metabolites were mainly enriched in purine metabolism, phenylpropanoid biosynthesis, the shikimate pathway, and tryptophan metabolism. Flavonoid biosynthesis was significantly induced only in leaves. Moderate N deficiency benefits carbohydrate and specialized metabolites accumulations, whereas decrease the most amino acid accumulation (except for L-tryptophan). N-deficient treatments induced the synthesis and accumulation of quality indicators (indigo-indirubin, epigoitrin and anthranilic acid) in a certain degree.